2021
DOI: 10.1080/21645515.2021.1984124
|View full text |Cite
|
Sign up to set email alerts
|

Real-world evidence for the effectiveness and breakthrough of BNT162b2 mRNA COVID-19 vaccine at a medical center in Japan

Abstract: Evidence of BNT126b2 vaccine effectiveness and breakthrough has been primarily demonstrated in populations outside of Asia; studies in the Western Pacific region are limited. Our retrospective cohort study assessed SARS-CoV-2 cases after vaccine rollout starting from mid-March 2021 at a tertiary hospital in Tokyo. Of 8,749 staff members, no fully vaccinated staff demonstrated confirmed infection, versus 19 cases in unvaccinated or partially vaccinated staff, by the end of June. Three breakthrough cases were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 3 publications
2
7
0
1
Order By: Relevance
“…This was confirmed by our observation that less than one-third of the subjects were able to display nAbs against the delta VoC at t 10m (Figure 3c). Similar observations were seen in cohorts studied by Katz et al [82] and Naito et al [83] who both observed an increase in BTI cases 3 and 5 months post-vaccination, respectively, during increased circulation of SARS-CoV-2 VoCs. In our opinion, this paves the way for an additional booster vaccine to restimulate waning immunity against SARS-CoV-2, especially in immunocompromised patients [84] or the frail elderly population.…”
Section: Discussionsupporting
confidence: 86%
“…This was confirmed by our observation that less than one-third of the subjects were able to display nAbs against the delta VoC at t 10m (Figure 3c). Similar observations were seen in cohorts studied by Katz et al [82] and Naito et al [83] who both observed an increase in BTI cases 3 and 5 months post-vaccination, respectively, during increased circulation of SARS-CoV-2 VoCs. In our opinion, this paves the way for an additional booster vaccine to restimulate waning immunity against SARS-CoV-2, especially in immunocompromised patients [84] or the frail elderly population.…”
Section: Discussionsupporting
confidence: 86%
“…A major finding in our study is a of Ct values and LIAISON SARS-CoV-2 Ag levels highlighting no significant differences between vaccinated and unvaccinated individuals in term of viral RNA loads and SARS-CoV-2 Ag levels, suggesting the same transmission potential. These data seem to be in line with several previous investigations showing no significant differences between vaccinated and unvaccinated groups, with significant breakthrough infections of SARS-CoV-2 variants in fully vaccinated people [33,[35][36][37][38][39][40][41]. However, previous studies showed that COVID-19 vaccines attenuated the SARS-CoV-2 RNA loads, indicating a reduced infectiousness and virus transmissibility [17,18,42].…”
Section: Discussionsupporting
confidence: 91%
“…Finally, 18 studies were included in the synthesis of the meta-analysis and systemic review. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Findings of each included study are described in Supporting Information: Table S3. S4 and Figures S2,3).…”
Section: Resultsmentioning
confidence: 99%
“…The PRISMA flow model for study selection is shown in Supporting Information: Figure . Finally, 18 studies were included in the synthesis of the meta‐analysis and systemic review 4–21 . Findings of each included study are described in Supporting Information: Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation